2016
DOI: 10.1002/ptr.5739
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Dermatophyte and Anti‐Malassezia Activity of Extracts Rich in Polymeric Flavan‐3‐ols Obtained from Vitis vinifera Seeds

Abstract: Several human skin diseases are associated with fungi as dermatophytes and Malassezia. Skin mycoses are increasing and new alternatives to conventional treatments with improved efficacy and/or safety profiles are desirable. For the first time, the anti-dermatophytes and the anti-Malassezia activities of Vitis vinifera seed extracts obtained from different table and wine cultivars have been evaluated. Geometric minimal inhibitory concentration ranged from 20 to 97 µg/mL for dermatophytes and from 32 to 161 µg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…[39][40][41][42][43] Flavonoids and phenolic compounds are known to possess antimicrobial, anti-inflammatory, and antioxidant property. 5,[7][8][9] Studies have shown that leaf extracts rich in flavonoids are active against M. furfur. 5,[7][8][9] Recently, it has been shown that polyphenolic compounds, including flavonoids such as quercetin and kaempferol, show activity against Malassezia globosa by selectively inhibiting Malassezia b-carbonic anhydrase, a validated antidandruff target.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[39][40][41][42][43] Flavonoids and phenolic compounds are known to possess antimicrobial, anti-inflammatory, and antioxidant property. 5,[7][8][9] Studies have shown that leaf extracts rich in flavonoids are active against M. furfur. 5,[7][8][9] Recently, it has been shown that polyphenolic compounds, including flavonoids such as quercetin and kaempferol, show activity against Malassezia globosa by selectively inhibiting Malassezia b-carbonic anhydrase, a validated antidandruff target.…”
Section: Discussionmentioning
confidence: 99%
“…are responsible for a variety of cutaneous as well as systemic infections such as pityriasis versicolor, malassezia folliculitis, seborrheic dermatitis, dandruff, and atopic dermatitis. [2][3][5][6][7][8] Furthermore, Malassezia spp.induced skin inflammation can worsen the clinical symptoms of skin ailments such as psoriasis. 3 Finally, the ability of Malassezia spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The aetiological agents and clinical manifestations of superficial mycoses vary between regions and depend on the socioeconomic status of the patients. Dermatophytoses are common superficial infectious diseases caused by dermatophytes, pathogenic fungi which digest keratin ( Trichophyton, Epidermophyton and Microsporum ) and affect about 20%–30% of human population worldwide . Dermatophytes cause 90% of toenail and 50% of fingernail onychomycosis cases, while 5%–11% of onychomycoses are of mixed aetiology, including both dermatophytes and moulds.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of superficial mycoses is also a long and often unsuccessful process. Among antifungal agents recommended in superficial infections treatment, there are azoles, morpholines, allylamines, ciclopirox, polyenic and non‐polyenic antibiotics …”
Section: Introductionmentioning
confidence: 99%